Student Volunteers, Post-Flood Recovery, Psychosocial Support, Community Engagement, School Rehabilitation Psychosocial Support and Student Volunteer Action in Post-Flood Recovery in Samudra Subdistrict, North Aceh Regency - mardiaton Mardiaton; Nur Afni Yunita; sri mulyati; hilmi; Ikhyanuddin; Nur Elisyah; Yashifa Aulia; Siti Nazila Azizi (Jurnal Pengabdian Bakti Akademisi, 2026)
The flood disaster in Samudra Subdistrict, North Aceh Regency, caused significant disruption to social, educational, and psychological conditions within the affected communities. This Student Creativity Program (PKM) was designed to provide humanitarian assistance through the active involvement of student volunteers in three key activities: cleaning school facilities, distributing basic food supplies, and delivering psychosocial support to children and families. The implementation was carried out collaboratively with schools, village authorities, and local residents to ensure the effectiveness of the interventions. The outcomes demonstrated improved school readiness and cleanliness, fulfillment of basic needs through food distribution, and enhanced emotional resilience among survivors through psychosocial assistance. This PKM highlights the crucial role of student volunteers as agents of social change, contributing to post-disaster recovery through a multidimensional approach that integrates educational, social, and psychological support.